Organization of engineering works in deploying a bridge crossing point made of class 20 pontoon material - Kovačević, Nenad V. (Vojnotehnički glasnik / Military Technical Courier, 2015)
When using pontoon material for deploying a bridge crossing point and/or some other type of crossing of water obstacles (ferry, landing), it is very important to organize works during the preparation, construction and disengagement of pontoon units and materials for the deployment and maintenance of already deployed crossing points. In the Serbian Armed Forces (SAF) there are specialized units for such works within military engineering, pontoon battalions, and within the River Flotilla (brigade units). The organization of engineering works given in the article represents a method for finding solutions to the use of movable assets and personnel in establishing bridge crossing points (BCPs) made of pontoon materials with a capacity of 20 t. The lack of contemporary literature in drafting the basic documents for the establishment of BCPs (existing literature dates from the 70s and 80s of the last century) is only one of the problems encountered when working in this area so, in the preparation of project documentation, experience from practice is heavily relied upon.
Keywords: engineering units; engineering works; crossing over; pontoon materials